Environmental & architectural phenomenology. Vol. 24, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2013)
Vol. 24, No. 1, Winter 2013 (includes “items of interest,” book reviews by David Seamon, & Ingrid Leman Stefanovic and essays by Matthew Bower & Thomas Owen).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals